1087 A service evaluation of the impact of e-scooters on emergency departments in Bristol (The SEED Study). Issue 3 (21st February 2022) - Qandil, Sara; Roberts, Thomas; Dickinson, Thomas; Robinson, Carl; Watkins, Millie; Aubrey, Emily; Dulac, Emma; Willis, Henry; Lockyer, Andy; Lyttle, Mark; Carlton, Edward
Abstract : Aims/Objectives/Background: E-scooters have risen in popularity worldwide. However, e-scooter associated injuries have become a growing area of concern. In the UK, rental e-scooters became legalised in 2020, and have been rolled out in several UK cities. There is no published UK literature reporting e-scooter related injuries. This service evaluation aims to evaluate the impact of e-scooters on Emergency Departments (ED) within one UK city. Methods/Design: Between May to June 2021, we conducted an approved (CE:74681) prospective observational service evaluation for a 4-week period across three EDs; one Adult Major Trauma centre (MTC), one city-centre Trauma Unit and one Paediatric MTC. All patients presenting to ED with an injury associated with an e-scooter (driver, passenger or bystander) were identified prospectively. Data collected included information on context of injury event and key clinical variables. Data was entered onto the online platform REDCap, and exported into Excel for analysis. Descriptive statistics are presented. Results/Conclusions: Ninety patients with an e-scooter related injury presented to ED during the evaluation. Median age was 25 years (IQR, 20-33). Findings demonstrate head, upper limbs and lower limbs were commonly injured. Of the 19% who experienced a head injury, two patients sustained an intracranial haemorrhage and one a basal skull fracture. Fractures were diagnosed in 41% of patients. Only 7% of riders were helmeted and 28% were intoxicated with alcohol. In total 62 x-rays and 13 CTs were undertaken. Although the majority were discharged following minor injuries, 11% of patients required admission, including one major trauma. Whilst e-scooters are a convenient mode of transport, riders are vulnerable to traumatic injuries of varying severity. Notably, low rates of helmet use and high prevalence of alcohol intoxication, suggest a need for targeted public health interventions. Future large-scale research is required to better evidence injury patterns and severity, identify modifiable risk factors and inform policy.